The effects of oil price uncertainty on economic activities in South Africa - Junior T. Chiweza; Goodness C. Aye (Cogent Economics & Finance, 2018)
This paper investigates the link between oil price uncertainty shocks and key macroeconomic indicators of a net oil importing country, South Africa. Monthly data covering the period 1990:01 to 2015:12 is used. The Structural Vector Autoregressive (SVAR) methodology is applied incorporating realized volatility as an indicator of oil price uncertainty to investigate the short run effects of oil price uncertainty. The Generalised Impulse Response Functions (GIRF) analysis reveals that for most variables, oil price uncertainty shock has an adverse and persistent effect over time. Consistent with GIRF, the Generalised Forecast Error Variance Decompositions (GFEVDs) analysis also points out that oil price uncertainty shocks contributes substantially to variations in real output, inflation and various macroeconomic variables of South Africa. Therefore, SVAR analysis reveals the significant role of exogenous oil prices on the economy of South Africa when price uncertainty shocks exist. The policy implications of these findings are drawn.
Keywords: C32; E32; Q43; 330; oil price uncertainty; volatility; economic activities; short run; SVAR; South Africa